History of the Labour Party From 1914 - "Cole, G D H" (London, 1951)
This book gives a full account of the development of the British Labour Party from its emergence as a national influence in the first world war to its return to power with an effective majority after the second world war. The study includes an epilogue which surveys the achievements of the party in the years after the 1945 election. This title will be of interest to scholars and students of history and politics.
Keywords: Politics Parties